Server+ certification training guide - Jernigan, Elton (Pearson Certification, 2001)
If you're a candidate for Server+ certification, which measures essential competencies in advanced PC hardware issues such as RAID, SCSI, multiple CPUs, SANs, and much more, the Training Guide has what you need to pass. We have partnered with Elton Jernigan , a Subject Matter Expert (SME) of the initial Focus Group for development of the Server+ exam. He brings you an excellent resource that not only will help you pass the exam, but will also prove to be a handy, concise reference for managers and technicians who must select and implement hardware for network servers. You will benefit from Elton's insight as a 27-year veteran of the IT industry, including his experience as Director of Technology for the College of Business at Florida State University and as a senior computer trainer for the Beacon Institute for Learning. We make the most of your Server+ Certification study time by providing: Content that is organized according to each job dimension and exam objective Exam objectives that are clearly detailed and explained Study strategies to optimize your learning Exam tips that provide specific exam-related advice Step-by-step instructions that walk you through a task and help you learn faster Additional content sections with in-depth reference material Chapter summaries that review key concepts Key terms you'll need to understand Resource URLs that list web sites you can access for additional information on topics in each chapter Exercises that provide concrete experiences to reinforce learning Review questions and answers to assess your comprehension Sample exam questions that include answers and detailed explanations.